Political Brokers in Head of Village Elections (A Case Study in Sangal Village and Rantau Bangkiang Village, Central Kalimantan Province, Indonesia) - Novie Revlie Pioh; Jovano Deivid Palenewen; Katerina Bataha (Journal of Governance and Public Policy, 2024)
In Indonesia, the role of political brokers is a ubiquitous phenomenon in the context of electoral processes at all levels. A substantial body of research has been devoted to the study of political brokers in Indonesia. Nevertheless, research on political brokers at the rural level remains scarce. Accordingly, this study seeks to examine the role of political brokers in the context of village head elections, with a particular focus on the cases of Sanggal village and Rantau Bangkiang village in Central Kalimantan, Indonesia. This research employs qualitative methods to elucidate the phenomenon of political brokers in village head elections. The concepts of political brokers, patron-client relationships, and forms of patronage were employed to analyze the manner in which candidates provide resources to the public through the intermediary of brokers. The findings revealed that political brokers were not only involved in the electoral processes for general and regional heads, but also in those for village heads. Furthermore, this study revealed that brokers played a pivotal role in securing victories for candidates in village head elections. The benefits received by brokers from candidates were not solely material, such as monetary compensation and goods, but also encompassed connections and promises of involvement in the village development agenda. Despite the methodological limitations of this study, it makes a valuable contribution to the field of political brokerage research in Indonesia, particularly in the context of rural elections.